Esensi Metode Pendidikan Islam - sukma, kinana dwinta (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2023)
It is strongly connected to the strategies used throughout the teaching and learning process in education. A teacher has to master the technique in order to meet the predetermined objectives. Students will learn the required lesson material if the proper techniques are used, in line with the subject matter, the circumstances, and the current conditions. After realising the value of approaches and techniques in education, educators must be skilled in creating these strategies. Education professionals need to be aware of the benefits and drawbacks of each approach being utilised if they want to encourage students to be more critical and participatory in the learning process. The fact that pupils get their intended outcome with this strategy is the most crucial factor. This study's aim is to explain the kind of instructional practises used in Islamic schools.